(untitled) (Jurnal Orthopaedagogia, 2024)
A comprehensive understanding of children with intellectual disabilities is important, as it directly informs the provision of appropriate educational and instructional strategies for them. This study aimed to explore the concept of identification and assessment of children with intellectual disabilities, including the scope, techniques, and stages involved in the assessment process. This study used literature review method to examine various issues related to the topic under study. Enhancing reguler teachers’ pedagogical skill is essential in carrying out identification and assessment, ensuring that accurate assessment results lead to the provision of an appropriate educational services for children with intellectual disabilities in inclusive schools.